Trends in Dengue Fever Incidence in Tomohon City, North Sulawesi, Indonesia, 2021-2023 - Fakhrul Mubarak Ahmad; Ihsan Adi Sasono; Hamdawang (Journal of Health Science and Pharmacy, 2026)
Background: Maternal and child health are essential indicators for evaluating the health status of a population and assessing the effectiveness of health sector development. West Sulawesi Province, located in Eastern Indonesia, faces significant challenges in reducing maternal and infant mortality rates. Factors such as geographical accessibility, the availability of healthcare personnel, and various social determinants contribute to the distribution of maternal and neonatal mortality in this region. Objectives: This study aims to describe the distribution of maternal and infant mortality in West Sulawesi Province from 2017 to 2020, using secondary data obtained from the West Sulawesi Provincial Health Profile. Methods: A descriptive quantitative approach was employed in this study, analyzing secondary data sourced from the Health Profile of West Sulawesi Province. The data include the annual number of maternal and infant deaths, which were organized into tables and graphs for analysis. The trends and patterns observed were interpreted narratively to provide a comprehensive overview of the data. Results: Based on Chart 1, the highest trend in dengue fever cases occurred in 2018, with 115 reported cases. This increase may be attributed to several factors, including high rainfall, population density, and local behaviors. Conclusion: Dengue Hemorrhagic Fever (DHF) poses a significant health threat, as it can develop into a deadly epidemic. Recognizing the trends and factors influencing DHF incidence is crucial for implementing effective early prevention strategies. Environmental factors, such as high rainfall, along with population density and behavioral patterns, contribute to the high incidence of DHF in certain areas. Keywords: Dengue Hemorrhagic Fever, Dengue Virus, Aedes Aegypti, Trends, Indonesia